Mixing It Up: The Place of the Arts in Multidisciplinary Contexts - Maxwell, Kate (UiT Norges arktiske universitet, Det kunstfaglige fakultet, 2017)
Artikkel i FoU-magasin fra Universitetet i Tromsø In this era of change, when the placement of the arts is coming under scrutiny at local, national, and international levels, the time seems right to explore the role of the artist (broadly understood) in multidisciplinary contexts. What can we offer, what can others offer us, and how can such partnerships succeed?